Description of a rheophilic Tilapia species Smith, 1840 (Teleostei: Cichlidae) from Guinea with comments on Tilapia rheophila Daget, 1962 - Dunz, Andreas R.; Schliewen, Ulrich K. (Zootaxa, 2012)
Tilapia konkourensis, new species, is described on the basis of three specimens from the upper Konkouré River and itstributary Kakrima. The rheophilic species differs from all other Tilapia sensu lato except T. fusiforme Dunz & Schliewen,2010 in a shallower body 30.0–31.5% vs. 32.9–52.5% SL and from T. fusiforme in having eight instead of nine to twelvelower lateral-line scales. It is most similar to Tilapia rheophila Daget, 1962, type species of the monotypic subgenus Tila-pia (Dagetia) Thys van den Audenaerde, 1969. An evaluation of the putative autapomorphies diagnosing Dagetia re-vealed that all are shared with members of the subgenus Coptodon Gervais, 1853 sensu Thys van den Audenaerde, 1969; hence, Tilapia (Dagetia) is placed in the synonymy of Tilapia (Coptodon).